Etične dileme pri (celostni) rehabilitaciji pacientov s sindromom kritično bolnega - Novak, Primož (Rehabilitacija (Ljubljana), 2017)
The rising number of postintensive care syndrome patients has brought about increasing need for their rehabilitation. Dilemmas regarding the admission of such patients are linked with the subjective assessment of their momentary capability for participating in comprehensive rehabilitation programmes, as well as with the concern about providing safe environment at our department. In cases of additional medical problems during rehabilitation, the question about the extent of diagnosing and treating those problems arises. Because psychological problems often present, the ethical dilemma about the efficiency of rehabilitation during the absence of the only ward psychologist arises. In cases of infringement of hospital rules by the patient or the patient%s violent behaviour we have to make a difficult choice between the patient%s right to rehabilitation and the protection of other patients and staff. Dilemmas at discharge arise mostly when the patient does not achieve the desired goals and/or there are doubts regarding suitability of his/her home environment.
Keywords: Critical Illness; ethical issues; ethics; etične dileme; Post-intensive care syndrome; rehabilitacija; Rehabilitation; sindrom kritično bolnega; vocational rehabilitation